Investigation on the Effect of Nanoparticle Diameter and Concentration on the Performance of Nanofluid Solar Pond - Ting, S.Y.Y. (Institute of Physics, 2022)
The usage of brine water in solar pond has triggered concern on its potential to pollute surrounding land ecosystem. Thus, non-toxic non-polluting nanofluid is proposed to replace brine water in solar pond. No study on it has been reported. This study is therefore conducted to evaluate the performance of density gradient nanofluid solar pond. An experimental test rig is built to conduct this evaluation. The nanoparticle used in this study is the widely available nontoxic silicon oxide (SiO2). The effect of nanoparticle diameter and concentration on the solar pond performance is evaluated. The results firmly indicate the potential of SiO2 nanofluid in replacing the brine water. In addition, it was found that both nanoparticle diameter and concentration affect the thermal storage performance. Â© The Electrochemical Society